Comparison of effects of mild heat combined with lactic acid on Shiga toxin producing Escherichia coli O157:H7, O103, O111, O145 and O26 inoculated to spinach and soybean sprout - Dikici, Abdullah; Koluman, Ahmet; Calicioglu, Mehmet (Elsevier Sci Ltd, 2015)
The aim of the present study was to investigate the effect of lactic acid against Shiga toxin producing Escherichia coli (O157:1-17 and non-O157 serogroups including O103, O111, O145 and O26) at different conditions. Soybean sprouts and spinach leaves inoculated with each serogroup of E. coli (similar to 7.00 + 1.00 log(10) cfu/g) were treated with the lactic acid solutions at different concentrations (0% (control), 1.5%, 2.0%, or 2.5%) and at different temperatures (20, 40, or 50 degrees C) for 3 min. Results indicated that regardless of the treatment temperature, no significant reduction in the numbers of any serogroup occurred in the control group (0%) (p > 0.05). However, lactic acid at concentration of 1.5%, 2% and 2.5% was found to be effective against all organisms tested. There was no significant difference (p > 0.05) between E. coli O157:H7 and non-O157 STEC serogroups at any treatment group. The highest reductions (ca. 400 log(10) cfu/g) of all serotypes in both produces were observed after immersing into 2.5% lactic acid at 50 degrees C. The results of this study showed that decontamination of fresh produces such as spinach and soybean sprout with lactic acid solutions prepared at mild temperatures (40 degrees C and 50 degrees C) might be an effective safety measure in preventing public health risks associated with these products contaminated with STEC. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fresh produce; Decontamination; E. coli O157:H7; Non-O157 Shiga toxin-producing E. coli; Mild heat; Organic acids